2022
DOI: 10.4103/jomfp.jomfp_333_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary oxidative stress in oral lichen planus using malonaldehyde

Abstract: Background: Oral lichen planus is a chronic, mucocutaneous, inflammatory disease, with an unknown etiology. Reactive oxygen species and oxidative damage to the tissues might be the cause. Malonaldehyde (MDA), a low molecular weight end product of lipid peroxidation reaction is a suitable biomarker of endogenous DNA damage. monitoring the oxidant-antioxidant status of saliva may serve as an efficient marker of disease development in oral lichen planus patients. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There are many ways cigarettes are sold, such as in tins, cartons, packs, "kiddie" packs, and loose sticks [5]. Small cigarette pack sizes (hereafter referred to as kiddie packs) consist of less than 20 cigarette sticks per pack [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways cigarettes are sold, such as in tins, cartons, packs, "kiddie" packs, and loose sticks [5]. Small cigarette pack sizes (hereafter referred to as kiddie packs) consist of less than 20 cigarette sticks per pack [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is still a lack of experimental evidence for a causal relationship between pack size and consumption [10]. On the other hand, the affordability of kiddie packs would encourage smoking among the lower income groups, mainly teens and minors [5]. This would demean efforts in combating tobacco consumption, as numerous studies have shown that tobacco consumption dropped in response to higher prices [11][12][13].…”
Section: Introductionmentioning
confidence: 99%